Integrated FEM-Multibody Co-Simulation of Additively Manufactured Hip Prosthesis containing cracks. - Domenico Gentile; Roberto Di Bona; Giuseppe Peter Vanoli; Gabriel testa; Sara Ricci (Fracture and Structural Integrity)
The increase in life expectancy and attention to the quality of life of elderly people spurred the need, in the last decades, to increase the capabilities of medical and surgical techniques. Among these, the development of prosthetic implants has been a staple of biomedical engineering research since the 70’s. In order to satisfy the challenging demands, the latest novelties in industrial engineering are being tested in their applicability to subjects. The 3D printing of metal alloys can produce a highly customizable product, which, after the proper heat treatments, can possess adequate mechanical properties to ensure a satisfactory component life. Defective products are often the results of wrong or absent post-processing treatments which may cause an uncontrolled crack propagation and a premature total failure of the implant. The behavior of such a product, with various critical crack conditions, was investigated by an integrated MBD-FEM co-simulation environment, focused on a femur subjected to total hip replacement. It was concluded that the Stress Intensity Factor (SIF) computed by the model is compatible with the premature failures experienced by patients, and as such, this model opens the possibility for further analyses aimed at understanding the role of defects on the durability of prothesis